2021
DOI: 10.21203/rs.3.rs-416973/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Awake Prone Positioning in Patients with Hypoxemic Respiratory Failure Due to COVID-19: The PROFLO Multicenter Randomized Clinical Trial

Abstract: Background: The effect of awake prone positioning on intubation rates is not established. The aim of this trial was to investigate if a protocol for awake prone positioning reduces the rate of endotracheal intubation compared with standard care among patients with moderate to severe hypoxemic respiratory failure due to COVID-19. Methods: We conducted a multicenter randomized controlled trial. Adult patients with confirmed COVID-19, high-flow nasal oxygen or noninvasive ventilation for respiratory support and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…Finally, 22 studies with a total of 5146 patients were included in the meta-analysis. [21][22][23][24][25][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 22 studies with a total of 5146 patients were included in the meta-analysis. [21][22][23][24][25][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]…”
Section: Search Resultsmentioning
confidence: 99%
“…The sample size ranged from 20 to 1121 patients. Seven of these studies were RCTs, 21,22,24,25,[30][31][32] of which one was a randomized, controlled, multinational, metatrial. 21 The other fifteen were observational studies.…”
Section: Study Characteristics and Risk Of Biasmentioning
confidence: 99%
“…In another multicenter, multifactorial trial, Rosén et al randomized patients not only to HFNO or NIV, but also to standard care (i.e., supine/semi-recumbent position) versus APP. 56 PaO 2 /FiO 2 at inclusion was again in the range of moderate-to-severe ARDS, and noninvasive supports had a failure rate of 33% in both standard care and proned patients, without differences in terms of need for intubation. Lastly, a recent review and meta-analysis by Kharat et al on prone positioning in intubated and nonintubated patients showed a reduction in intubation rate for patients undergoing APP outside the ICU (OR: 0.60 [95% CI: 0.38–0.95]) and a reduction in mortality when APP was applied in the ICU (OR: 0.49 [95% CI: 0.32–0.77]).…”
Section: Noninvasive Ventilation In Covid-19 Patientsmentioning
confidence: 92%
“…Zur Sicherstellung einer ausreichenden Oxygenierung bei ARDS hat sich neben nichtinvasiver Beatmung (NIV), High-Flow-Sauerstofftherapie und invasiver Beatmung die BL als effektive Therapiesäule etabliert 2 5 6 . Neue prospektive Daten aus randomisiert kontrollierten Studien zur Behandlung von COVID-19-Patient:innen mit ARDS zeigen vorteilhafte Effekte einer zusätzlichen BL bereits während der Phase nichtinvasiver Beatmung 7 8 9 . In der S3-Leitlinie zur stationären Therapie von COVID-19 wird bei High-Flow-Sauerstofftherapie und CPAP („continuous positive airway pressure“)/NIV zusätzlich eine BL empfohlen 9 .…”
Section: Hintergrundunclassified